An Overview of Torture Prevention Systems in Russia, Lithuania, Sweden and Norway - Herbert, Tania (Torture Journal, 2020)
The very nature of detention means that those subjected to it are dependent on detaining authorities to provide protection and to refrain from human rights abuses, including torture and ill treatment. Recognising this, the Optional Protocol to the UN Convention against Torture (OPCAT) obliges signatories to establish detention monitoring bodies through National Preventative Mechanisms (NPMs). Whilst some regions have received considerable attention in terms of CAT and OPCAT compliance, this has not generally been so for the region incorporating Russia, Nordic and Baltic countries.